The quality management sourcebook : an international guide to materials and resources - Avery, Christine (Routledge, 1997)
The concept of Quality Management began in the manufacturing sector, but a growing concern with quality in other areas of the economy has led to its wider application in service industries, government, education, and other not-for-profit agencies. A great quantity of material related to quality management has been produced in recent years, much of it by small presses, professional and trade associations, and consultants. The Quality Management Sourcebook is the first in-depth, international guide to the most useful material and sources of information. The book begins with the origi.